Can the Lamberts and Lambert submaximal cycle test reflect overreaching in professional pyclists? - Decroix, L.; Lamberts, R. P.; Meeusen, R. (International Journal of Sports Physiology and Performance, 2018)
Context: The Lamberts and Lambert Submaximal Cycle Test (LSCT) consists of 3 stages during which cyclists cycle for 6 min at 60%, 6 min at 80%, and 3 min at 90% of their maximal heart rate, followed by 1-min recovery. Purpose: To determine if the LSCT is able to reflect a state of functional overreaching in professional female cyclists during an 8-d training camp and the following recovery days. Methods: Six professional female cyclists performed an LSCT on days 1, 5, and 8 of the training camp and 3 d after the training camp. During each stage of the LSCT, power output and rating of perceived exertion (RPE) were determined. Training diaries and Profile of Mood States (POMS) were also completed. Results: At the middle and the end of the training camp, increased power output during the 2nd and 3rd stages of the LSCT was accompanied with increased RPE during these stages and/or the inability to reach 90% of maximal heart rate. All athletes reported increased feelings of fatigue and muscle soreness, while changes in energy balance, calculated from the POMS, were less indicative of a state of overreaching. After 3 d of recovery, all parameters of the LSCT returned to baseline, indicating a state of functional overreaching during the training camp. Conclusion: The LSCT is able to reflect a state of overreaching in elite professional female cyclists during an 8-d training camp and the following recovery days.